(untitled) (Physical Sciences and Technology, 2016)
Thin films of aluminum-doped zinc oxide (AZO) were prepared using magnetron sputtering and atomic layer deposition (ALD) techniques. Atomic force microscopy (AFM) studies of AZO films surface morphology show that the surface of produced by ALDfilms is a smoother in comparison with films formed by magnetron sputtering.According to comparative analysis of optical transmittance spectra in the visible range of 300 - 800 nm, films formed by ALD technique demonstrates 10% higher transparency than those that obtained by magnetron sputtering. Investigation of samples electrical properties show that the conductivity of AZO films obtained by ALD technique actually two orders of magnitude higher than analogues obtained by magnetron sputtering.